Solve for h 88+36=(8/38)(h-5)

Math
88+36=(838)(h-5)
Rewrite the equation as (838)(h-5)=88+36.
(838)(h-5)=88+36
Multiply both sides of the equation by 388.
388⋅((838)(h-5))=388⋅(88+36)
Simplify both sides of the equation.
Tap for more steps…
Simplify 388⋅((838)(h-5)).
Tap for more steps…
Cancel the common factor of 38 and 8.
Tap for more steps…
Factor 2 out of 38.
2(19)8⋅((838)(h-5))=388⋅(88+36)
Cancel the common factors.
Tap for more steps…
Factor 2 out of 8.
2⋅192⋅4⋅((838)(h-5))=388⋅(88+36)
Cancel the common factor.
2⋅192⋅4⋅((838)(h-5))=388⋅(88+36)
Rewrite the expression.
194⋅((838)(h-5))=388⋅(88+36)
194⋅((838)(h-5))=388⋅(88+36)
194⋅((838)(h-5))=388⋅(88+36)
Cancel the common factor of 8 and 38.
Tap for more steps…
Factor 2 out of 8.
194⋅(2(4)38(h-5))=388⋅(88+36)
Cancel the common factors.
Tap for more steps…
Factor 2 out of 38.
194⋅(2⋅42⋅19(h-5))=388⋅(88+36)
Cancel the common factor.
194⋅(2⋅42⋅19(h-5))=388⋅(88+36)
Rewrite the expression.
194⋅(419(h-5))=388⋅(88+36)
194⋅(419(h-5))=388⋅(88+36)
194⋅(419(h-5))=388⋅(88+36)
Apply the distributive property.
194⋅(419h+419⋅-5)=388⋅(88+36)
Combine 419 and h.
194⋅(4h19+419⋅-5)=388⋅(88+36)
Multiply 419⋅-5.
Tap for more steps…
Combine 419 and -5.
194⋅(4h19+4⋅-519)=388⋅(88+36)
Multiply 4 by -5.
194⋅(4h19+-2019)=388⋅(88+36)
194⋅(4h19+-2019)=388⋅(88+36)
Move the negative in front of the fraction.
194⋅(4h19-2019)=388⋅(88+36)
Apply the distributive property.
194⋅4h19+194(-2019)=388⋅(88+36)
Cancel the common factor of 19.
Tap for more steps…
Cancel the common factor.
194⋅4h19+194(-2019)=388⋅(88+36)
Rewrite the expression.
14(4h)+194(-2019)=388⋅(88+36)
14(4h)+194(-2019)=388⋅(88+36)
Cancel the common factor of 4.
Tap for more steps…
Factor 4 out of 4h.
14(4(h))+194(-2019)=388⋅(88+36)
Cancel the common factor.
14(4h)+194(-2019)=388⋅(88+36)
Rewrite the expression.
h+194(-2019)=388⋅(88+36)
h+194(-2019)=388⋅(88+36)
Cancel the common factor of 19.
Tap for more steps…
Move the leading negative in -2019 into the numerator.
h+194⋅-2019=388⋅(88+36)
Cancel the common factor.
h+194⋅-2019=388⋅(88+36)
Rewrite the expression.
h+14⋅-20=388⋅(88+36)
h+14⋅-20=388⋅(88+36)
Cancel the common factor of 4.
Tap for more steps…
Factor 4 out of -20.
h+14⋅(4(-5))=388⋅(88+36)
Cancel the common factor.
h+14⋅(4⋅-5)=388⋅(88+36)
Rewrite the expression.
h-5=388⋅(88+36)
h-5=388⋅(88+36)
h-5=388⋅(88+36)
Simplify 388⋅(88+36).
Tap for more steps…
Cancel the common factor of 38 and 8.
Tap for more steps…
Factor 2 out of 38.
h-5=2(19)8⋅(88+36)
Cancel the common factors.
Tap for more steps…
Factor 2 out of 8.
h-5=2⋅192⋅4⋅(88+36)
Cancel the common factor.
h-5=2⋅192⋅4⋅(88+36)
Rewrite the expression.
h-5=194⋅(88+36)
h-5=194⋅(88+36)
h-5=194⋅(88+36)
Add 88 and 36.
h-5=194⋅124
Cancel the common factor of 4.
Tap for more steps…
Factor 4 out of 124.
h-5=194⋅(4(31))
Cancel the common factor.
h-5=194⋅(4⋅31)
Rewrite the expression.
h-5=19⋅31
h-5=19⋅31
Multiply 19 by 31.
h-5=589
h-5=589
h-5=589
Move all terms not containing h to the right side of the equation.
Tap for more steps…
Add 5 to both sides of the equation.
h=589+5
Add 589 and 5.
h=594
h=594
Solve for h 88+36=(8/38)(h-5)

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top